METAPREV: Holistic empowerment program for nursing homes integrated with a website to reduce metabolic syndrome in the elderly - Aisyah Al Mahiroh; Salsabila Firamadhani; Putri Hanifah; Astrid Belinda Nuraini Mudomy; Muhammad Arya Putra Rhiswanto; Firman (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Panti Werdha Hargo Dedali Surabaya is a social welfare institution for the elderly established in 1987, located at Jalan Manyar Kartika IX, Sukolilo, Surabaya, East Java. The institution faces serious challenges, where the initial screening of 29 elderly residents revealed a high incidence of Metabolic Syndrome (MS) indicators, aggravated by the absence of a structured program supporting a healthy lifestyle. Methods: Its implementation methodology utilizes the CBPR approach, comprising: 1) Coordination with partners, 2) Validation of partner need, 3) Creation of intervention media, 4) Activity implementation, and 5) Evaluation and cadres. Findings: The results of the Metaprev program are highly significant: the elderly experienced an improvement in health categories, with an increase in MS knowledge (93%) and TOGA processing skills (98%), alongside the establishment of new routine exercises and yoga. The Metaprev Website now functions optimally as a user-friendly monitoring tool. Sustainability is ensured through the formation of 7 Meta SEHAT Cadres. Conclusion: The Metaprev program successfully reduced the risk of metabolic syndrome and empowered older adults through integrated health education, digital monitoring, and sustainability led by healthcare professionals. This comprehensive approach provides a replicable and effective model for improving geriatric preventive care and promoting healthy aging in social welfare institutions. Novelty/Originality of this article: Metaprev is proven effective in significantly improving the healthy lifestyle and reducing the rate of Metabolic Syndrome.